PENYELESAIAN SENGKETA HARTA GONO-GINI PASCA PERCERAIAN: ANALISIS KAJIAN PUSTAKA TERHADAP KETIDAKPASTIAN HUKUM PEMBAGIAN HARTA BAWAAN YANG TERCAMPUR DENGAN HARTA BERSAMA DALAM YURISPRUDENSI MAHKAMAH AGUNG RI - Gunawan Widjaja (INTELIGENSIA MEDIA, 2026)
This article aims to analyze the resolution of disputes over marital property following divorce, with a focus on the legal uncertainty surrounding the division of separate property that has been commingled with marital property in the case law of the Supreme Court of the Republic of Indonesia. This issue is important to examine because Indonesian marriage law essentially stipulates that assets acquired during marriage constitute joint property, while separate property remains under the control of each party; however, this provision has not provided detailed criteria regarding the legal status of separate property that has merged or become integrated into the household’s economic life. Consequently, disputes over the division of assets following divorce often lead to differing interpretations, both regarding the standard of proof and in judicial deliberations, particularly when determining the boundary between individual and joint rights over an asset. This study employs a literature review method with a normative legal approach. The findings conclude that legal uncertainty in the division of separate property that has been commingled with joint property stems from the absence of clear normative parameters regarding the form of commingling, the extent of each party’s contribution, and uniform evidentiary standards in judicial practice. Therefore, there is a need to strengthen regulations and develop more operational judicial guidelines so that the resolution of post-divorce marital property disputes not only reflects substantive justice but also ensures legal certainty and consistency in judicial decisions within the Indonesian judicial system.